Emission optimised control and speed limit for isolated intersections. Issue 3 (6th April 2017) - Blokpoel, Robbin; Hausberger, Stefan; Krajzewicz, Daniel
Abstract : Stopping and accelerating at traffic lights is one of the main contributing factors to vehicular emissions in urban environments. The work in this study demonstrates a generic guideline for minimising CO2 emissions at traffic lights. This was done using an adaptive control, which uses a cost function for optimisation, rather than network‐specific control parameters. A new version of the emission model PHEMlight was used, which added of a fuel cut‐off mode during coasting and other improvements compared with the previous version. Using this model, it could be determined that the emission optimal ratio between delay time and stops for the cost function of an adaptive control should be 1:165 at 50 km/h. When the speed limit increases the ratio also increases with 1:296 for 70 km/h. However, it was also found that the optimal free flow travel speed was around 70 km/h. Therefore, with long distances between intersections and a low amount of average stops, the maximum speed should be higher than 50 km/h for emission optimality. Application of the ratio for 50 km/h to the adaptive control algorithm ImFlow resulted in a CO2 emission reduction of 6.3% compared with a vehicle actuated control.